Antitumor Effects of Berberine on Gliomas via Inactivation of Caspase-1-Mediated IL-1β and IL-18 Release - Lei Tong; Chuncheng Xie; Yafen Wei; Yunyue Qu; Hongsheng Liang; Yiwei Zhang; Tianye Xu; Xin Qian; Huijia Qiu; Haoyu Deng (Frontiers in Oncology, 2019)
Gliomas arise in the glial cells of the brain or spine and are the most prevalent and devastating type of brain tumors. Studies of tumor immunology have established the importance of the tumor micro-environment as a driver of oncogenesis. Inflammatory mediators such as IL-1β and IL-18 released by monocytes regulate transcriptional networks that are required for malignant cell growth. Berberine is a natural botanical alkaloid that is widely found in the Berberis species. Although it has been widely used as an anti-diarrheal treatment in North America for several decades, our study is the first to investigate berberine as an anti-tumor agent in glioma cells. In this study, we demonstrate that berberine significantly inhibits inflammatory cytokine Caspase-1 activation via ERK1/2 signaling and subsequent production of IL-1β and IL-18 by glioma cells. Moreover, we found that berberine treatment led to decreased motility and subsequently cell death in U251 and U87 cells. In addition, our study is the first to indicate that berberine can reverse the process of epithelial-mesenchymal transition, a marker of tumor invasion. Taken together, our work supports berberine as a putative anti-tumor agent targeting glioma cells.